A NEW PERSPECTIVE ON THE SOCIAL CAUSES AND RESEARCH METHODS IMPACTING PREMATURE BIRTH - Kamolova F. E.; Djurayev J. A.; Akhundjanov N. A.; Narmurotov B. K.; Yusupov Sh. Sh. (Web of Journals Publishing, 2024)
A lot of methods for studying premature babies are given and analyzes based on modern technologies are considered. The data of research literature in Russian in the cyberleninka.ru, e LIBRARY electronic search engines in the Scopus international databases for the period 2018-2022 were processed and analyzed.
Keywords: Premature baby, Neonatal jaundice, Pregnancy, artificial lung ventilation, Birth.